Chitin and Collagen: Isolation, Purification, Characterization, and Applications (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
This reprint includes recent trends in all aspects of applied scientific research on chitin and collagen, including isolation, purification, and characterization. A few recent innovations in chitin and collagen have been incorporated into this reprint. These innovations could potentially be applied in various scientific and industrial research. Due to its broad array of biological functions such as anticancer, antimicrobial, bone tissue regeneration, antioxidant, and anti-aging activities, collagen has recently attracted vast interest in the pharmaceutical, nutraceutical, and cosmeceutical industries. Similarly, chitin and chitin-derived chitosan have many applications, including in the medical, environmental, and agricultural sectors.